2006
DOI: 10.1007/s10815-006-9082-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy prediction models and eSET criteria for IVF patients–do we need more information?

Abstract: Purpose: The purpose of the present study was to evaluate statistical prediction models and simple allocation criteria, based on predictors for pregnancy, as tools to identify a good prognosis group in a possible eSET setting.Methods: A pregnancy prediction model based on logistic regression models was generated by analysis of 1675 DET treatment cycles. The model was evaluated and compared to simple eSET allocation criteria.Results: Embryo quality, patient age, and basal FSH were identified as significant pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 47 publications
5
46
0
3
Order By: Relevance
“…23 In this study it is observed that effect of ovarian aging on FORT is negligible as compared to PFC, basal E2 and FSH levels and antral follicles continue to respond to FSH irrespective of ovarian aging which is supported by other studies. 11,24 The present study reflected that high peak E2 (at the time of OI) is associated with greater number of oocytes maturity, retrieval, fertilization, cleavage and the number of top quality embryos which enhance chances of clinical pregnancy as observed in other studies 14,25 The suggested high peak E2 for improvement of oocyte and embryo quality was observed in high FORT group of our study, similar results were shown in another study. 26,27 The increased E2 produced by growing follicles in the window of implantation, increases endometrial receptivity by apposition, attachment and apposition for the encroaching blastocyst.…”
Section: Discussionsupporting
confidence: 90%
“…23 In this study it is observed that effect of ovarian aging on FORT is negligible as compared to PFC, basal E2 and FSH levels and antral follicles continue to respond to FSH irrespective of ovarian aging which is supported by other studies. 11,24 The present study reflected that high peak E2 (at the time of OI) is associated with greater number of oocytes maturity, retrieval, fertilization, cleavage and the number of top quality embryos which enhance chances of clinical pregnancy as observed in other studies 14,25 The suggested high peak E2 for improvement of oocyte and embryo quality was observed in high FORT group of our study, similar results were shown in another study. 26,27 The increased E2 produced by growing follicles in the window of implantation, increases endometrial receptivity by apposition, attachment and apposition for the encroaching blastocyst.…”
Section: Discussionsupporting
confidence: 90%
“…Two embryonic variables, the total number of good-quality embryos and total number of embryos, ranked as the most important and second most important predictors of clinical pregnancy chance after a completed IVF/ICSI cycle (Table III). Most previous studies focused on the quality and number of transferred embryos because they aimed at the outcome of fresh cycles (Terriou et al, 2001;Hunault et al, 2002;Lee et al, 2006;Ottosen et al, 2007). We used the total number of good-quality embryos and total number of embryos to assess the quality and quantity of all the embryos from one ovarian stimulated cycle in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro fertilization (IVF) has become a commonly used ART since the first birth after IVF-embryo transfer on 25 July 1978, the IVF process still remains a difficult one for the infertile couples with low success rates on the first attempt. Furthermore, the high twin pregnancy rate arising from IVF has been recognized as a significant public health issue leading, in many countries, to policies encouraging or mandating increased use of single-embryo transfer (SET) (Hunault et al, 2002;Ledger et al, 2006;Ottosen et al, 2007;Roberts et al, 2009). These factors have led to a need to study further predictors and to evaluate the probability of a patient achieving a pregnancy as accurately as possible before and during the course of her IVF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…çalışmalarında hem bazal FSH'nın hem de yaş faktörünün IVF performansında etkili olduğunu belirtmişlerdir (18) . Yapılan diğer çalışmalarda bazal FSH'sı 0-10 IU/1 ve 10 IU/1'den yüksek olan hastalar iki grupta değerlendirilmiş ve bazal FSH'sı 0-10 IU/1 olan kadınlarda gebelik şansının daha yüksek olduğu bildirilmiştir (19,20) . Bizim çalışmamızda, gebe (7,9±2,1) ve gebe olmayan (8,3±4,0) grupların bazal FSH değerleri karşılaştırıldığında bu değerin gebelik oluşumunu istatistiksel olarak anlamlı etkilemediği görülmüştür.…”
Section: Discussionunclassified